2014
DOI: 10.1093/nar/gku200
|View full text |Cite|
|
Sign up to set email alerts
|

Human RECQL1 participates in telomere maintenance

Abstract: A variety of human tumors employ alternative and recombination-mediated lengthening for telomere maintenance (ALT). Human RecQ helicases, such as BLM and WRN, can efficiently unwind alternate/secondary structures during telomere replication and/or recombination. Here, we report a novel role for RECQL1, the most abundant human RecQ helicase but functionally least studied, in telomere maintenance. RECQL1 associates with telomeres in ALT cells and actively resolves telomeric D-loops and Holliday junction substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 72 publications
(141 reference statements)
4
27
0
Order By: Relevance
“…Consistent with our observation, Popuri et al [53] have recently reported that RECQ1 associates with telomeres in ALT cells and its interaction with TRF2 regulates its helicase activity on telomeric DNA in vitro . We used a 15 nt 5’-flap substrate containing (TTAGGG) 4 sequence that has been previously reported to be bound by TRF2 [41] to ask whether RECQ1 can stimulate FEN-1 activity on telomeric DNA (Figure 8C, D).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our observation, Popuri et al [53] have recently reported that RECQ1 associates with telomeres in ALT cells and its interaction with TRF2 regulates its helicase activity on telomeric DNA in vitro . We used a 15 nt 5’-flap substrate containing (TTAGGG) 4 sequence that has been previously reported to be bound by TRF2 [41] to ask whether RECQ1 can stimulate FEN-1 activity on telomeric DNA (Figure 8C, D).…”
Section: Resultssupporting
confidence: 93%
“…A qPCR based analysis of telomere length revealed that RECQ1-KD cells have shorter telomeres than shCTL HeLa cells (48.31 vs 52.82 kb, P= 0.038) (Figure 9E). This observation is qualitatively consistent with a recent report using Q-FISH analysis in RECQ1-depleted HeLa cells, however the magnitude of difference in telomere length in Popuri et al [53] is substantially greater and may be attributed to different assay methods used. To further characterize this system, γH2AX immunoprecipitates were analyzed.…”
Section: Resultssupporting
confidence: 92%
“…WRN likely has a function at telomeres and can form a complex with SMARCAL1 (37); however, WRN knockdown did not cause C-circle formation. RTEL1 has at least two essential telomere functions, although we have not detected any interaction between RTEL1 and SMARCAL1 (34,38). It will be important to understand how these helicases work cooperatively to achieve successful telomere replication.…”
Section: Discussionmentioning
confidence: 81%
“…Recent evidence suggests a potential role of RECQ1 in telomere metabolism (43). The ability of RPA to stimulate RECQ1 removal of the catalytically inactive BamHI mutant protein bound to a DNA substrate suggested RPA may also stimulate RECQ1 displacement of the shelterin proteins TRF1 and TRF2 bound to the telomeric duplex sequence.…”
Section: Rpa Stimulates Fancj-or Recq1-catalyzed Displacement Of Trf1mentioning
confidence: 99%